ANALISIS KINERJA PEGAWAI PADA KANTOR KELURAHAN GILINGAN KOTA SURAKARTA - Isma Agnes Savelin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This type of research is qualitative research. The data sources in this study are primary and secondary data. This study has 10 informants consisting of key informants (Lurah), triangulation informants (5 employees) and supporting informants (4 communities). The informant determination technique uses purposive sampling, namely sampling carried out by selecting subjects based on the specification criteria set by the researcher. Data collection techniques in this study are interviews, observations and documentation. Data were collected through interviews with informants and validity tests using source triangulation so that the data obtained is valid. Data analysis techniques in this study use data reduction, data presentation and drawing conclusions.The results of this study conclude that the performance of employees in Gilingan Village is quite good in providing services to the public. However, maintain and continuously improve service quality, it is recommended that the Village conduct regular training and conduct routine and structured performance evaluations.